HARMONIZATION IMPLEMENTATION OF CURRENT USP REQUIREMENT AND GAMP ON INSTRUMENT QUALIFICATION IN RESEARCH AND DEVELOPMENT LABORATORY WITH RISK MANAGEMENT APPROACH - Kusuma Dewi Yatisantoso, Tias
Based on the requirement of the latest United State Pharmacopeia (USP), chapter 21 Code of Federal Regulation (CFR) part 11, and International Society for Pharmaceutical Engineering Good Automated Manufacturing Practice (ISPE GAMP), qualification of analytical instrument is the most basic things needed to acquire a high quality analytical result and ensure data integrity. However the implementation of these requirements still need interpretation and technical approach and hence the aim of this research was to establish a technical guideline for the implementation of those requirements in a research and development laboratory of a pharmaceutical industry. The research was initiated with determining parameters needed to plan qualification of analytical instruments followed by development of the strategic flow chart of qualification plan and application simulation of this plan in actual laboratory conditions. The level of qualification activities and the extend of risk-based control were parameters included to plan qualification of analytical instruments. The strategic flow chart of qualification plan was developed by means of the following steps: creating a technical description of instrument and system inventory, categorization of analytical instrument and system, and application of Process and Data Integrity Centric. Simulation based on result of desk review was conducted using data and system available on 2019. The gap analysis showed that qualification fulfilment for analog instrument, instrument witfh simple software, instrument with embedded calculation, instrument with user defined program and computerized instrument with configured system were 100, 100, 76, 0, and 13%, respectively. In the case of data integrity technical control, the fulfillment levels of 21 CFR part 11 for chromatography data system and UV-VIS spectrophotometry software were 78.3 and 69.6%, respectively. Based on the overall results, it was concluded that the technical guideline for the implementation of the above-mentioned requirements to acquire high quality analytical result and ensure data integrity was successfully established and applicable for a research and development laboratory of a pharmaceutical industry.